Pengembangan Inovasi Pembelajaran Digital Menggunakan Model Blended POE2WE di Era Revolusi Industri 4.0 - Nana Nana; Endang Surahman (Universitas Sebelas Maret, 2019)
Abstract: Developing digital learning innovation with the Blended POE2WE model aims (1) to access knowledge without time and space limitation, (2) to establish internet-based communication, (3) to make learning easier and more enjoyable, and (4) to create more interactive and innovative learning process. The method was literacy (library study). Electronic Data Processing was used to manipulate data into more useful information. Data is a raw object, not processed yet and going to be processed. Meanwhile, information is processed data and becomes other useful data. Digital learning is the product of industrial revolution 4.0. It deals with a large collection of computers in networks that are tied together so that many users can share their vast resources. Besides, the Prediction, Observation, Explanation, Elaboration, Write and Evaluation (POE2WE) learning model was developed from the POEW learning model and the Physics learning model with a constructivist approach. As a consequence, Blended Learning is used to synthesize face-to-face learning and online-based learning into an integrated mix so that can create a high, efficient, and attractive impact. Blended learning practically means that learning (classroom-based learning) is also facilitated with other electronic formats (e-learning) to create an optimal learning program. This is due to that the use of e-learning is very superior compared to Conventional Learning (face-to-face).Abstrak: Pengembangan inovasi pembelajaran digital dengan model Blended POE2WE bertujuan untuk (1) mengakses pengetahuan setiap saat tak terbatas waktu dan tempat (2) menjalin komunikasi berbasis internet (3) menciptakan pembelajaran lebih mudah dan menyenangkan. (4) menciptakan proses pembelajaran lebih interaktif dan inovati. Metode penelitian yang digunakan adalah literasi (studi pustaka). Pengolaan Data Elektronik digunakan untuk memanipulasi data menjadi suatu informasi yang lebih berguna. Data merupakan objek mentah, yang belum diolah dan akan diolah. Sedangkan, informasi adalah data yang telah diolah dan sifatnya menjadi data lain yang bermanfaat. Pembelajaran digital adalah produk revolusi industry 4.0. Pembelajaran digital merupakan ‘a large collection of computers in networks that are tied together so that many users can share their vast resources’. Selain itu, model pembelajaran Prediction, Observation, Explanation, Elaboration, Write dan Evaluation (POE2WE) dikembangkan dari model pembelajaran POEW dan model pembelajaran Fisika dengan Pendekatan Konstruktivistik. Oleh karena itu, Blended Learning digunakan untuk mensintesis pembelajaran tatap muka dan pembelajaran berbasis online menjadi satu campuran yang terintegrasi sehingga dapat menciptakan dampak yang tinggi, efisien, dan menarik. Secara praktis, blended learning berarti bahwa pembelajaran (pembelajaran tatap muka dalam kelas) juga dilengkapi dengan format elektronik lainnya (e-learning) untuk membuat suatu program pembelajaran yang optimal. Hal ini disebabkan karena pemanfaatan E-Learning sangat diunggulkan dibanding dengan Pembelajaran Konvensional secara tatap muka.